Aspekt prawny przy zakażeniu gronkowcem złocistym w placówce medycznej = Legal aspect of the Staphylococcus aureus infection in a medical facility - Siminska, Joanna; Martyna, Specjał; Nowacki, Michał; Rosenau, Dominik; Porzych, Piotr; Głowacka, Iwona; Beuth, Wojciech (Journal of Education, Health and Sport, 2017)
Siminska Joanna, Specjał Martyna, Nowacki Michał, Rosenau Dominik, Porzych Piotr, Głowacka Iwona, Beuth Wojciech. Aspekt prawny przy zakażeniu gronkowcem złocistym w placówce medycznej = Legal aspect of the Staphylococcus aureus infection in a medical facility. Journal of Education, Health and Sport. 2016;6(11):179-183. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.164984 http://ojs.ukw.edu.pl/index.php/johs/article/view/3979 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 22.10.2016. Revised 30.10.2016. Accepted: 07.11.2016. Aspekt prawny przy zakażeniu gronkowcem złocistym w placówce medycznej Legal aspect of the Staphylococcus aureus infection in a medical facility Joanna Siminska1, Martyna Specjał2, Michał Nowacki2, Dominik Rosenau2, Piotr Porzych1, Iwona Głowacka1, Wojciech Beuth3 1 Katedra i Klinika Rehabilitacji Collegium Medicum UMK w Bydgoszczy 2 Kancelaria Radcy Prawnego Michał Nowacki 3 Wojewódzki Szpital Specjalistyczny we Włocławku, Oddział Neurochirurgii Streszczenie Gronkowiec złocisty (Staphylococcus aureus) w mikrobiologii definiowany jest jako najbardziej chorobotwórczy gatunek wśród gronkowców. Gronkowiec złocisty dzięki zdolnościom dużej wirulencji, nabywania oporności na antybiotyki, jak również środki dezynfekcyjne i antyseptyczne stał się obecnie głównym czynnikiem etiologicznym zakażeń szpitalnych o ciężkim przebiegu. Zagadnienie zakażeń szpitalnych, jest zagadnieniem dość kontrowersyjnym opiewającym na zbiegu dwóch praw. Prawa medycznego i cywilnego. Jest to niezwykle ważny termin, zarówno z punktu widzenia medycznego, prawnego jak i społecznego. Słowa kluczowe: gronkowiec złocisty, zakażenie szpitalne, aspekty prawne, prawo Summary The Staphylococcus aureus (Staphylococcus aureus) in microbiology is defined as the most pathogenic species among the staphylococci. Staphylococcus aureus with high capacity of virulence, to acquire resistance to antibiotics, as well as disinfectants and antiseptics became now the main etiological factor nosocomial infections severe. The issue of hospital infections, is quite a controversial issue costing a confluence of two rights. Medical law and civil law. This is an extremely important concept, both from the point of view of the medical, legal and social. Keywords: Staphylococcus aureus, nosocomial infection, legal aspects, right